Serum carcinoembryonic antigen (CEA) as a clinical marker in acquired idiopathic generalized anhidrosis: a close correlation between serum CEA level and disease activity. (7th October 2015) - Honma, M.; Iinuma, S.; Kanno, K.; Komatsu, S.; Minami‐Hori, M.; Iizuka, H.; Ishida‐Yamamoto, A.
Abstract: Background: Hypohidrosis/anhidrosis are congenital or acquired sweating impairments. Among them, acquired idiopathic generalized anhidrosis/hypohidrosis (AIGA) is the most common, and characterized by favourable response to systemic corticosteroid, however, no clinical markers for disease severity or activity have been developed. Objective: Our aim was to verify the usefulness of serum carcinoembryonic antigen (CEA) level monitoring as a clinical marker for disease activity of AIGA. Methods: Ten cases of AIGA diagnosed at Asahikawa Medical University, from 1980 to 2014 were included in the study. CEA and/or CEACAM1 expression level was analysed using immunohistochemistry and enzyme‐linked immunosorbent assay. Result: CEA expression was restricted to the apical membrane of glandular cells in eccrine sweat glands in most of the three types of cases we examined [healthy control, patients with atopic dermatitis (AD) or urticaria]. However, CEA expression was detected diffusely and much more intensively in eight of the 10 AIGA cases included in this study. CEACAM1‐expression was much more restricted on the apical membrane of glandular cells of both the AIGA cases and the other control subjects. While serum CEA levels increased in all five AIGA cases examined (5.8–43.2 ng/mL), it remained within normal limits in all control subjects: nine healthy individuals; 10 cases of AD; 10 cases of idiopathic urticaria; four cases of normohidrotic cholinergic urticaria (Mann–Whitney's U ‐test, P < 0.05). The increased serum CEA levels in AIGA decreased in conjunction with improved sweating during methyl prednisolone pulse therapy or repeated bathing. Conclusion: Serum CEA level may serve as a clinical marker for AIGA activity.